Effects of fluoxetine-induced hyperprolactinaemia on adenomyosis induction in Wistar Albino rats - (:unkn) unknown (CHAPMAN HALL LTD, 1996)
Fluoxetine, a serotonin reuptake inhibitors was administered to groups of overiectomised and intact Wistar rats for 14 weeks. Controls received a placebo. At the end of the experimental period the animals were decapitated. Prolactin was measured in the separated plasma and the uteri examined by light microscopy. Prolactin levels were significantly higher in those rats treated with fluoxetine. 11 out of 12 intact rats given fluoxetine exhibited endometrial stromal invasion. It is suggested that high circulating levels of prolactin lead to degeneration of myometrial cells in the presence of ovarian steroids. This could result in myometrial invasion by endometrial stroma and eventually progress to adenomyosis.
Keywords: adenomyosis; fluoxetine; hyperprolactinaemia; UTERINE ADENOMYOSIS; PROLACTIN; MICE; RELEASE